First confirmed case of nasal pythiosis in a horse in Thailand. (9th January 2018) - Tonpitak, Walaiporn; Pathomsakulwong, Watcharapol; Sornklien, Chulabha; Krajaejun, Theerapong; Wutthiwithayaphong, Suppathat
Abstract : Introduction. Pythiosis is caused by Pythium insidiosum, a fungus-like organism in the class Oomycetes . It can infect humans and a variety of animal species in tropical, subtropical and some temperate regions. Cases of animal pythiosis have occurred predominantly in horses in the skin and subcutaneous tissue at the limbs and in the ventral portion of thoracoabdominal wall - lesions in the nasal region are rarely reported. Moreover, although many human pythiosis cases have been reported in Thailand, no cases of animal pythiosis in Thailand have been reported. Case presentation. We report a case of pythiosis in a horse infected at the nasal cavity. Diagnosis was performed by zoospore formation by bait technique, immunohistochemical stain, immunochromatography and sequence analysis. Conclusion. The sequences of rDNA were 99 % and 96 to 99 % identical to GenBank isolates of Pythium insidiosum from two Thai human patients and horses from various countries, respectively. This represents the first confirmed report of nasal equine pythiosis in Thailand.